Are Recent Arctic Ozone Losses Caused by Increasing Greenhouse Gases? - Rieder, Harald; Polvani, Lorenzo M. (2013)
It has been suggested that the Arctic ozone losses observed in recent years might be a manifestation of climate change due to increasing greenhouse gases. We here offer evidence to the contrary, by focusing on the volume of polar stratospheric clouds (Vpsc), a convenient proxy for polar ozone loss whose simplicity allows for easily reproducible results. First, we analyze the time series of Vpsc in three reanalysis data sets and find no statistically significant trends in Vpsc–nor changes in their probability density functions–over the period 1979–2011. Second, we analyze Vpsc in a stratosphere-resolving chemistry-climate model forced uniquely with increasing greenhouse gases following the A1B scenario: here too, we find no significant changes in Vpsc over the entire 21st century. Taken together, these results strongly suggest that the sporadic high ozone losses in recent years have not been caused by increasing greenhouse gases.